Personal characteristics and leadership soft skills affecting the knowledge management of public health officers in Udon Thani provincial public health office - Kromsang, Pranchanok; Jutarosaga, Makarapan; Bouphan , Prachak; Phimha, Surachai (Journal of Medical and Public Health Region 4, 2023)
This cross-sectional descriptive research aimed to study the personal characteristics and leadership soft skills affecting the knowledge management of public health officers in Udon Thani provincial public health office, Thailand. A set of 159 public health officers was randomly selected by stratified random sampling. Data was collected by the questionnaire that examined and verified by three experts for content validity item objective congruence (IOC), all items were more than 0.50, the reliability of the questionnaire had a Cronbach’s alpha coefficient was 0.98, and used the in-depth interview guidelines with 14 key informants. Data was collected between 6th December 2022 to 6th January 2023. Data analysis was performed by Pearson’s Product Moment Correlation Coefficient and Stepwise Multiple Linear Regression Analysis. The results showed that the overall level of leadership soft skills, and the knowledge management were at a high level with averages of 3.92 (S.D.=0.54) and 3.69 (S.D.= 0.68), respectively. The overall of leadership soft skills had a high level of relationship with the knowledge management with r=0.843 (p-value<0.001). Five variables composed of leadership soft skills ; presentation, planning and organizing, coaching skills and initiative skills that affected and could jointly predicted the knowledge management of public health officers in Udon Thani provincial public health office at 71.4 percentage (Adjusted R2=0.714, p-value<0.001). From in-depth interviews by the interviewees is that some employees still lack skills in effective communication to ensure understanding by others. Additionally, skills in organizational planning more crucial at the forefront. In order to develop practical plans for their assigned tasks. Teaching skills were though creatively to innovate and improve work processes. Therefore, it was recommended that management. This will contribute to transforming the organization into a learning organization.